Does Mandatory Pressure Increase RFID Adoption? A Case Study of Western Australian Livestock Industry - Hossain, Mohammad; Quaddus, Mohammed (Springer, 2013)
Radio Frequency Identification (RFID) technology has been increasingly used in innovative applications around the world. It has caught attention of different industries and been mandated by resource dominant organizations and different countries in various applications. In Australia RFID is mandatory for cattle identification. The objective of this research is to investigate whether the mandatory pressure really makes the livestock farms to adopt RFID. This study took the broader aspect of external environment considering external pressure, external support, and external uncertainty. Applying a mixed method approach this is a prime initiative exploring and detailing the external environmental factors on RFID context. Following extensive literature on innovation and RFID adoption this paper, first, explores the relevant factors on miscellaneous innovations. The literature review was followed by a qualitative field study. The field study confirms and contextualizes the factors from the literature review. Finally, an empirical study investigates the adoption behavior of livestock farms in relation to RFID adoption in the context of Western Australia. Data were analyzed using Partial Least Square (PLS)-based Structured Equation Modeling (SEM) tool. The analysis finds that market pressure, cognitive pressure, government support, and external uncertainty are the main driving factors in RFID adoption. Implications of the results are highlighted.